Prediction of the minimum fluidization velocity of particles of sugarcane bagasse - Pérez, Nestor Proenza [UNESP] (2018)
This study refers to an experimental analysis of the fluid-dynamics of particles of sugarcane bagasse in a fluidization column with an internal diameter of 190 mm, which determined the minimum fluidization velocity of the particles with different characteristic diameters (0 < dp<9.5 mm), using air as fluidization means. The results have shown that the minimum fluidization velocity has a tendency to increase as the diameter of the particle increases. However, in a certain range of diameter (0.88 mm < dp<9.5 mm), where the particles have a high aspect ratio (length/diameter), it has not been possible to fluidize them. High superficial air velocities have been used, mainly due to the strong trend to interlace and to develop high adhesion forces in this type of particles, as well as the high porosity that is displayed. Based on the experimental results, two new models have been developed in order to determine the minimum fluidization velocity and the complete fluidization velocity of the sugarcane bagasse with diameters that range from 0.075 to 0.445 mm. The comparisons have been made by using correlations from the literature for the determination of the minimum fluidization velocity, and the experimental results have shown that the new suggested correlations finely predict this parameter, with a maximum error range of 6%, respecting the experimental values.